A broadband and high-efficiency polarization conversion metasurface. Issue 2 (17th February 2022) - Geng, Yanfeng; Ding, Mengjie; Zuo, Jiankang; Chen, Xinwei; Han, Liping; Han, Guorui
ABSTRACT: In this paper, a broadband and high-efficiency polarization conversion metasurface (PCM) is proposed. It is composed of the patch layer, two layers of dielectric substrates and the ground plane. The patch layer is formed by hexagonal patches etched with open-loop gaps. Also, the hexagonal patches are printed on the diagonal of the unit of PCM that the polarization direction of the incident wave is rotated 90°. In order to improve the efficiency of polarization conversion, two different dielectric substrates are used to achieve impedance matching between the PCM and the free space. In addition, through introducing the open-loop gap in the center of the hexagonal patch, multiple resonant frequencies are generated. Therefore, the conversion bandwidth is further expanded. Simulated and measured results show that the polarization conversion ratio (PCR) of the proposed metasurface is higher than 90% from 7.4 to 17.0 GHz. Especially, the PCR can reach 100% at the resonant frequencies.